Jewish studies underground in Leningrad in the 1980s. - Beizer, Michael (East European Jewish Affairs, 2018)
This article is a first-hand report of a participant and leader of a number of underground initiatives within the “refuseniks’” community which aimed to encourage Jewish studies. These underground initiatives involved seminars (scholarly as well as public), excursions through Jewish historical sites, and the publication of a samizdat journal. In short, these initiatives sought to recover and disseminate knowledge of Jewish history and culture.